Model for Absorption of Perfluoropropane Intraocular Gas after Retinal Surgeries - Bahill, A Terry (International Journal of Medical and Health Sciences Research, 2016)
Purpose: The intended audience for this paper is retina surgeons who perform retinal detachment (RD) operations, anesthesiologists and dentists who use nitrous oxide, ophthalmologists and optometrists who encounter RD patients, students of ophthalmology and optometry, and RD patients, their families and friends. To help future retinal detachment (RD) and macular hole patients understand imminent eerie visual events, the author developed a mathematical model for the behavior of an injected intraocular C3F8 perfluoropropane gas bubble after an RD operation. Ophthalmologists could use this model to create animations showing patients what to expect. Methods: Our subject had three RD operations with the injection of perfluoropropane gas. After each of these operations, he daily recorded the horizon to gas bubble angle and the radius of curvature of the gas bubble. These data were used to calculate the volume and surface area of the gas bubble. Then formal modeling techniques were applied. Results:One gas bubble, which lasted 73 days, was studied extensively. Fitting the measured data required four geometric submodels, corresponding to the four possible bubble configurations. Conclusions: This model for the absorption of an intraocular gas bubble had two components: the structural component described the four geometric configurations that the bubble went through in its lifecycle and the dynamic component that described the absorption rate of the gas. The model suggests that the gas-bubble absorption-rate is not proportional to either the surface area of the bubble or the surface area between the SF6 gas and the aqueous humour. Rather the gas-bubble absorption-rate is proportional to the surface area of gas in contact with the retina.